Nurses’ knowledge, attitudes, and practices toward breastfeeding in neonatal care: a survey - Li, Chunjie; Cai, Liangli; Zhang, Qing; Wu, Longyan (Frontiers in Pediatrics, 2026)
BackgroundBreastfeeding promotion is a cornerstone of neonatal nursing, as it plays a pivotal role in safeguarding the health and fostering the development of newborns. This study aimed to assess neonatal nurses’ Knowledge, Attitudes, and Practices (KAP) regarding breastfeeding for hospitalized neonates and identify factors influencing these domains.MethodsA cross-sectional survey was conducted among neonatal nurses between July 1 and August 30, 2025. Eligible nurses were recruited via a rigorous screening process, and data were collected using a validated KAP scale. Benjamini-Hochberg false discovery rate (FDR) adjustment addressed multiple comparison biases, and comprehensive regression assumption checks (multicollinearity, residual normality, homoscedasticity) were performed to ensure result validity.ResultsA total of 122 neonatal nurses were included. Based on predefined scoring benchmarks (Low: ≤90; Moderate: 91–140; High: ≥141), participants demonstrated a moderate level of overall breastfeeding-related KAP (mean ± SD: 134.28 ± 14.02). Hierarchical regression analysis revealed: (1) Knowledge was significantly predicted by age (β = 0.304, p = 0.017), years of clinical experience (β = 0.433, p = 0.040), educational level (β = 0.385, p = 0.015), and specialized breastfeeding training (β = 0.402, p = 0.007); (2) Attitudes were significantly influenced by number of children (β = 0.224, p = 0.018), professional title (β = 0.196, p = 0.002), and specialized training (β = 0.264, p = 0.001); (3) Practices were significantly associated with years of clinical experience (β = 0.380, p = 0.028), professional title (β = 0.504, p = 0.011), educational level (β = 0.436, p = 0.020), and specialized training (β = 0.329, p = 0.001). Specialized breastfeeding training emerged as a consistent positive predictor across all KAP dimensions (medium effect sizes), explaining 56.0%–63.6% of the variance in the models (adjusted R2).ConclusionNeonatal nurses exhibited positive attitudes but moderate knowledge and practice levels regarding breastfeeding, with targeted gaps in evidence-based care and parental education. These findings highlight the need for tailored training programs—prioritizing younger nurses, those with less experience, lower educational/professional titles, and untrained individuals—to enhance breastfeeding-related competence.